Comparisons of High‐Linear Energy Transfer Spectra on the ISS and in Deep Space. Issue 3 (1st March 2019) - Zeitlin, C.; Narici, L.; Rios, R. R.; Rizzo, A.; Stoffle, N.; Hassler, D. M.; Ehresmann, B.; Wimmer‐Schweingruber, R. F.; Guo, J.; Schwadron, N. A.; Spence, H. E.
Abstract: In deep space, personnel and equipment are exposed to the space radiation environment in the form of energetic particles, specifically galactic cosmic rays and sporadic solar energetic particle events. Radiation fields resulting from these particles are modified by shielding, but most radiation measurements in deep space have been made with detectors that were unshielded or very lightly shielded. In contrast, the space radiation environment on the International Space Station (ISS) is more complicated, with time‐dependent modification of the incident flux by the geomagnetic field and complex bulk shielding distributions; measured particle spectra inside the ISS are affected by both types of shielding. The geomagnetic field is also responsible for the existence of the South Atlantic Anomaly, a region of trapped energetic protons and electrons, and hence enhanced radiation dose, through which the ISS travels several times per day on average. Here our primary aim is to compare charged‐particle spectra at high linear energy transfer obtained by the Anomalous Long‐Term Effects in Astronauts instrument on ISS during high‐latitude portions of the orbit to data acquired at the same time by the Cosmic Ray Telescope for the Effects of Radiation and Radiation Assessment Detector instruments, both in deep space. The hypothesis being tested is that these spectra are the same, modulo shielding differences, since the effects of the geomagnetic field are expected to be minimal at high latitudes. Plain Language Summary: Exposure to highly energetic particle radiation in space is a concern for current and future human missions. To date, only the Apollo astronauts have ventured outside the protective effects of the Earth's magnetic field, but astronauts on future missions back to the Moon, or to Mars or other destinations in deep space, will not have this protection. In the high‐latitude parts of the orbit of the International Space Station, the magnetic shielding is weak, and in principle we expect the radiation environment there to be very similar to that in deep space. Here we present the first direct test of this hypothesis, using data obtained by three different particle detectors, one aboard the ISS, one in lunar orbit, and one that was in interplanetary space between Earth and Mars for part of the time period being studied, and on the surface of Mars for the rest of the period of interest. Key Points: We report comparisons of energetic particle spectra taken in low‐Earth orbit at high geomagnetic latitudes to similar data from deep space Three instruments were used in the study, one aboard the International Space Station, one in lunar orbit, and one in interplanetary space Despite shielding differences, the spectra have many features in common, but fluxes aboard the Space Station are slightly smaller